How to Improve Inflation Targeting in Canada - Obstfeld, Maurice (IMF Working Papers; Working Paper ;, 2016)
Routine publication of the forecast path for the policy interest rate (i.e. 'conventional forward guidance') would improve the transparency of monetary policy. It would also improve policy effectiveness through its influence on expectations, particularly when there is a risk of low inflation, and the policy rate is constrained by the effective lower bound. Model simulations indicate that a potent macroeconomic strategy, for returning the Canadian economy to potential, combines conventional forward guidance with a fiscal stimulus. As a response to the effective lower bound constraint, and the decline in the world equilibrium real interest rate, this strategy is preferable to raising the inflation target.